Linking mainland Australia and Tasmania using ambient seismic noise tomography: Implications for the tectonic evolution of the east Gondwana margin - Pilia, S.; Rawlinson, N.; Direen, N.G.; Reading, A.M.; Cayley, R.; Pryer, L.; Arroucau, P.; Duffett, M. (Gondwana Research, 2015)
For nearly half a century, a number of conflicting tectonic models have been postulated to explain the enigmatic geological relationship between Tasmania and Victoria, with a view to unifying our understanding of the evolution of the eastern margin of Gondwana in Australia. In this study, ambient noise data from an array of 24 broadband seismometers is used to produce a high-resolution 3-D crustal shear wave velocity model of Bass Strait, the key to understanding the missing link. We apply a novel transdimensional and hierarchical Bayesian inversion approach to construct group velocity maps in the period range of 2-30 s, and subsequently invert group velocity dispersion for 3-D shear wave velocity structure. This allows us to image, for the first time, the entire crust beneath Bass Strait in high detail and elucidate the geometry and position of key crustal features with corroboration from complementary datasets. The three sedimentary basins related to the failed rifting event associated with the Australia-Antarctica breakup, in particular Bass Basin, clearly emerge from the tomographic solution model. A key feature of the 3-D shear wavespeed model is a distinct mid-lower crustal NW-SE high velocity zone which extends from northwestern Tasmania to south-central Victoria, confirming a Proterozoic geological connection. We also image three north-south high velocity belts that appear to span Bass Strait, with some interruption from velocity variations possibly related to more recent tectonic events. These belts are consistent with recent gravity and magnetic maps, and may indicate the presence of an exotic Precambrian terrane (the Selwyn Block). The model also images the crustal velocity structure of the southern Stawell and Bendigo Zones, and their internal large-scale multi-layer characters, a legacy of their Early Paleozoic intra-oceanic origins. Another high velocity anomaly imaged in the mid-lower crust is an east-west lineament beneath the northern part of Bass Strait, which may be an intrusive feature associated with the failed rift. Â© 2014 International Association for Gondwana Research.